Treatment Adherence to Antiretroviral Therapy (ART) Among Human Immuno Deficiency Virus (HIV) Patients Attending the ART Centre; Kailali, Nepal : A Mixed Method Study - Dhami, Pawan Prakash; Khanal, Sita; Khanal, Kabita; Giri, Sunita; Wing Kandace, Chan Chi; Devkota, Nishchal (Annapurna Journal of Health Sciences, 2025)
Introduction: Antiretroviral Therapy (ART) is life saver and key determinant for prognosis and quality of life for Human Immune Deficiency Virus (HIV) infected patients, reduced disease progression rate and death. Maintaining optimal adherence level aimed for long term poses significant challenge for both patients and healthcare provider. Method: A cross-sectional facility based mixed method study was conducted, measuring 240 ART-prescribed patients and 6 in-depth interviews of service providers. Adherence was assessed through self-report from interviews. Bivariate analysis model was used to find factors associated with adherence, accompanied by thematic analysis of interview records. Results: Adherence level was 82.8% (n=197); 83.04% in male and 81.1% in female respectively. The reasons for non-adherence were forgetting (72.8%), busy schedule (41.9%), distant ART center (11.1%), travelled out (11.1%) and acute illness (7.4%). Monthly family income, illicit drug use, treatment satisfaction and duration of drug intake were significantly associated with adherence status. Factors associated with adherence were unemployment, drug abuse, duration of drug intake, side effect, stigma and discrimination, LTFU (Loss to Follow-up) cases, poverty, and education. Conclusion: The level of ART adherence among is unsatisfactory. Despite free access to ART medicine, it remains a major challenge to achieve complete adherence.